Evans Civit, J. H. (ed.). Antología del Index Aristotélicus de H. Bonitz. Buenos Aires, Santiago Arcos Editor, Colección Instrumentos, 2010. 637 pp. - Aguirre de Zárate, Susana (2011)
Fil: Aguirre de Zárate, Susana. Universidad Nacional de Cuyo